Interaction Abstractions for Public Display Applications - Cardoso, Jorge C. S. (2015)
Public digital displays have become increasingly ubiquitous in our technological landscape. Considering their flexibility and communication potential, public displays can become an important communication channel and even reach the attention, usage, and relevance that smartphones have today. Interaction with public displays is recognised as a key element in making them more engaging and valuable, but most public display systems still do not support any interactive feature. A key reason behind this apparent paradox is the lack of efficient and clear abstractions for incorporating interactivity into public display applications. While interaction can be achieved for a specific display system with a particular interaction modality, the lack of proper inter- action abstractions means that there is too much specific work that needs to be done outside the core application functionality to support even basic forms of interaction. In this chapter, we analyse existing systems, extract the relevant information from an interaction point of view, and propose and describe interaction abstractions for public displays. These abstractions are then implemented into software frameworks and toolkits for general use. We start by identifying and characterising interaction tasks and controls that are appropriate for public display interaction. We then apply the identified tasks and controls into the development of software toolkits that programmers can use to easily incorporate interactive features into their public display applications.